2001
DOI: 10.23986/afsci.5707
|View full text |Cite
|
Sign up to set email alerts
|

Non-wood plants as raw material for pulp and paper

Abstract: This study was begun in 1990 when there was a marked shortage of short fibre raw material for the pulp industry. During the last ten years the situation has changed little, and the shortage is still apparent. It was estimated that 0.5 to 1 million hectares of arable land would be set aside from cultivation in Finland during this period. An alternative to using hardwoods in printing papers is non-wood fibres from herbaceous field crops. The study aimed at determining the feasibility of using non-wood plants as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 88 publications
1
43
0
1
Order By: Relevance
“…The proportion of fiber length to diameter which is suitable for paper production is about 100:1, while for textiles a typical fiber length is >1000:1 (Saijonkari-Pahkala 2008). In this study, Enhalus acoroides with 128:1 ratio indicated its suitability in papermaking, and the value is slightly higher compared to 125:1 for Cyperus papyrus (Hurter 1990;Saijonkari-Pahkala 2008). In contrast, Halophila ovalis has wider fiber diameter (20.87 µm), lumen diameter (6.91 µm), and cell wall thickness (7.81 µm) compared to others.…”
Section: Fiber Dimensions and Derived Valuedmentioning
confidence: 77%
See 3 more Smart Citations
“…The proportion of fiber length to diameter which is suitable for paper production is about 100:1, while for textiles a typical fiber length is >1000:1 (Saijonkari-Pahkala 2008). In this study, Enhalus acoroides with 128:1 ratio indicated its suitability in papermaking, and the value is slightly higher compared to 125:1 for Cyperus papyrus (Hurter 1990;Saijonkari-Pahkala 2008). In contrast, Halophila ovalis has wider fiber diameter (20.87 µm), lumen diameter (6.91 µm), and cell wall thickness (7.81 µm) compared to others.…”
Section: Fiber Dimensions and Derived Valuedmentioning
confidence: 77%
“…Some nonwood fibers contain more pentosans (>20%), holocellulose (>70%), and less lignin (≃15%) compared to hardwoods (Hunsigi 1989). In addition, the higher hot water solubility characteristic possessed by non-wood plants ease the cooking liquors accessibility (Saijonkari-Pahkala 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…La principal fuente de fibra para la fabricación de pasta y de papel es la madera de coníferas y de especies arbóreas de hoja caduca. Fuentes secundarias son la paja de trigo, el centeno y el arroz; el bagazo de caña de azúcar; los tallos leñosos del bambú, lino y cáñamo, y fibras de semillas, hojas y cortezas, como las del algodón, el abacá y el henequén o sisal (Saijonkari, 2001).…”
Section: Introductionunclassified